Neuromarketing Reseach: Ethics, Procedures and Perceptions of Parties Involved - M.T. <U+021A>ichindelean (Вісник Київського національного університету імені Тараса Шевченка. Серія Економіка)
Through the present article neuromarketing as a research method is discussed, starting from definitions, to instruments available, ending with an analysis of the ethical issue of the field. The novelty of the study is that perceptions and experiences of neuromarketing practitioners are presented, therefore contributing to the knowledge creation regarding this type of marketing research.